Morphological and reproductive characterization of developed mutants in groundnut - M. A. Mondal, M.; S. H. Bhuiyan, M. (International Journal of Advanced Geosciences, 2020)
Twenty-eight established groundnut mutants and two check cultivars were studied during Kharif-I (March-June) season of 2017 and 2018 to find out their variability and distinct character(s) as identifying keys. All the mutant lines showed erect type sequential branching habits with two seeds in each pod although they had shown significant variability in all vegetative and reproductive structures. According to cluster analysis, 30 mutants/varieties clustered into three major groups at distance level 60 based on the morphological variability of 14 characters. The variability of 14 morphological characters in three principal components was explained by 98.12% of the total variation. The characters, 100-pod weight had the highest contribution followed by branch length, plant height and 100-kernel weight. Twenty-three mutant genotypes grouped into intermediate type of the extremes in any given identifying key characteristics. Only single genotype of the whole lot showed distinctively the longest primary branch and highest secondary branch number and small seed size (D1/24-29), highest primary branch number (M6/7-25), lowest primary branch number (Mut-2), highest leaflet length and light green leaf colour (Dhaka-1), presence of stem pigmentation and pod beak and highest number of seeds pod-1 (Zhingabadam), leaflet shape lanceolate (M6/54-20). In contrast, only two mutants of the lot showed two buds raceme-1 (M6/36-24 and M6/61-6), bolder pod and seed size and highly constricted pod (Mut-2 and Mut-3). The genotypes with the above distinguished characteristic featured for being ideal genetic markers and could be used in future breeding applications as well as aids in varietal identification.Â Â